Character Education for Santri Quality and Radicalism Prevention in Pesantren - Dewi Sadiah; Mustofa Mustofa (Yayasan Darusssalam Bengkulu, 2026)
This article examines character education as a strategy for developing santri quality and preventing radicalism at Pondok Pesantren Miftahul Huda Al Azhar Citangkolo, Banjar City. The study is framed as a continuing educational agenda in contemporary pesantren governance rather than as a response to a temporary crisis. It employs a qualitative case-study design with a descriptive-interpretive approach. Data were collected from kiai, teachers, alumni, institutional documents, observations, and interviews, and were analyzed through data reduction, data display, conclusion drawing, and verification. The findings show that santri quality is formed through pesantren regulations, the exemplary leadership of kiai and teachers, classical Islamic learning, Qur'anic memorization, Arabic and English language development, worship habituation, and the internalization of Ahlussunnah wal Jamaah values. The pedagogical methods include advice, discussion, demonstration, sorogan, bandungan, memorization, assignments, rewards, and sanctions. These practices strengthen discipline, reverence, positive thinking, religious literacy, and moral resilience. Character education in this pesantren functions as both academic formation and a preventive mechanism against radical religious tendencies.